Fungal diversity in grape must and wine fermentation assessed by massive sequencing, quantitative PCR and DGGE - Wang, Chunxiao; García-Fernández, David; Mas, Albert; Esteve-Zarzoso, Braulio (Frontiers in Microbiology, 2015)
The diversity of fungi in grape must and during wine fermentation was investigated in this study by culture-dependent and culture-independent techniques. Carignan and Grenache grapes were harvested from three vineyards in the Priorat region (Spain) in 2012, and nine samples were selected from the grape must after crushing and during wine fermentation. From culture-dependent techniques, 362 isolates were randomly selected and identified by 5.8S-ITS-RFLP and 26S-D1/D2 sequencing. Meanwhile, genomic DNA was extracted directly from the nine samples and analyzed by qPCR, DGGE and massive sequencing. The results indicated that grape must after crushing harbored a high species richness of fungi with Aspergillus tubingensis, Aureobasidium pullulans or Starmerella bacillaris as the dominant species. As fermentation proceeded, the species richness decreased, and yeasts such as Hanseniaspora uvarum, Starmerella bacillaris and Saccharomyces cerevisiae successively occupied the must samples. The “terroir” characteristics of the fungus population are more related to the location of the vineyard than to grape variety. Sulfur dioxide treatment caused a low effect on yeast diversity by similarity analysis. Because of the existence of large population of fungi on grape berries, massive sequencing was more appropriate to understand the fungal community in grape must after crushing than the other techniques used in this study. Suitable target sequences and databases were necessary for accurate evaluation of the community and the identification of species by the 454 pyrosequencing of amplicons.